Digitalisation For Sustainable Infrastructure: The Road Ahead - Secchi, Carlo (ISPI Publications, 2022)
In today's tumultuous and fast-changing times, digitalisation and technology are game changers in a wide range of sectors and have a tremendous impact on infrastructure. Roads, railways, electricity grids, aviation, and maritime transport are deeply affected by the digital and technological transition, with gains in terms of competitiveness, cost-reduction, and safety. Digitalisation is also a key tool for fostering global commitment towards sustainability, but the race for digital infrastructure is also a geopolitical one. As the world's largest economies are starting to adopt competitive strategies, a level playing field appears far from being agreed upon. Why are digitalisation and technology the core domains of global geopolitical competition? How are they changing the way infrastructure is built, operated, and maintained? To what extent will road, rail, air, and maritime transport change by virtue of digitalisation, artificial intelligence, and the Internet of Things? How to enhance cyber protection for critical infrastructure? What are the EU's, US' and China's digital strategies?